Environmental Change in Garibaldi Provincial Park, Southern Coast Mountains, British Columbia - Koch, Johannes; Menounos, Brian; Clague, John; Osborn, Gerald (Geoscience Canada, 2004)
SUMMARY We are reconstructing Holocene environments in Garibaldi Provincial Park, in the southern Coast Mountains of British Columbia, by examining a diverse set of paleoenvironmental records, including tree-rings, lake sediments, glacial landforms, and photographs. This integrated study, in combination with previous research in adjacent areas, is providing a more detailed picture of past climate, vegetation, and glacier extent in Garibaldi Park than has heretofore been available. The data suggest recurrent, complex, and successively more extensive glacier advances during the last half of the Holocene, followed by dramatic warming, snow and ice loss, and a rise in treeline in the twentieth century. The multi-proxy approach used in this study is broadly applicable to other mountain areas. It yields more reliable and robust paleoenvironmental reconstructions than approaches based on only one or two types of data.